Analisis Hukum Perikatan terhadap Wanprestasi dalam Perjanjian Jual Beli Kios: Studi Kasus Putusan Pengadilan Negeri Kupang Nomor 18/PDT.G/2016/PN.KPG - Raras Santika Arianti; Deva Anasthalia; Lintang Savana; Keysya Aurelia Putri Zakiyyati (Mahalini: Journal of Business Law, 2024)
This study aims to analyze the lack of clarity in legal considerations related to the case of kiosk seller default, which has the potential to cause legal uncertainty for the community. By analyzing this case, we can examine the application of the principles of contract law, such as the principle of freedom of contract and legal certainty, while also providing academic contributions in the form of critical evaluations of the decision. This study is also relevant to understanding how a sale and purchase agreement should be formulated to protect the rights and obligations of the parties, as well as to provide constructive suggestions for better legal practice. The research method used is normative juridical, which analyzes library materials or secondary data. In addition, a data triangulation method is applied to validate and improve the reliability of information by collecting data from various sources. This approach aims to gain a more comprehensive understanding and reduce bias that may arise from relying on one source or method. The conclusion is that: 1) The judge's considerations in deciding the case of default have been in accordance with applicable provisions based on the regulations; 2) The form of default is the delay and inconsistency between the agreement and the implementation of the agreement itself; and 3) The legal consequences received by Mrs. Dorce include payment of the remaining price of the kiosk, legal costs, responsibility for losses, and delay in recognizing ownership rights until her obligations are fulfilled.